Food Processing and Its Impact on Phenolic and other Bioactive Constituents in Food - Oszmianski, Jan; Lachowicz-Wiśniewska, Sabina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
It is our pleasure to present this Special Issue of Molecules entitled "Food Processing and Its Impact on Phenolic and other Bioactive Constituents in Food". Bioactive compounds including phenolic ingredients have long been used as important constituents of a healthy diet. As a result, consumer awareness about the important role of high-quality products rich in bioactive compounds-especially phenolic compounds-in human nutrition, health, and prevention against diseases has increased. Additionally, methods for food processing, regardless of the technology used, have a huge impact on the quality of the final products. Therefore, the big challenges for scientists lie in the monitoring of changes during food processing and the optimization of technology to achieve the minimal degradation of nutrients (including phenolic compounds). Thus, for this Special Issue, I encourage you to read some interesting papers aimed at bringing the latest scientific news, insights, and advances in the field of food processing and its impact on bioactive constituents in food, especially phenolic compounds. The information presented will certainly arouse considerable interest among a large group of our readers from different disciplines and research fields.